Beginning the Linux Command Line - Vugt, Sander. (Apress, 2009)
This is Linux for those of us who dont mind typing. All Linux users and administrators tend to like the flexibility and speed of Linux administration from the command line in bytesized chunks, instead of fairly standard graphical user interfaces. Beginning the Linux Command Line follows a taskoriented approach and is distribution-agnostic. Work with files and directories. Administer users and security. Understand how Linux is organized.